Sarmiento y su plan de gobierno para la Argentina: una aproximación a partir del estudio de la concepción del puerto en las ediciones del Facundo (Res Gesta, 2018)
The purpose of this work is to analyze the conception of the port in the editions of the book “Facundo” by Domingo Faustino Sarmiento. In 1845s and 1874s Facundo the role of the port, explained in the chapters XIV and XV, was the key because from there, solutions were projected to the troubles presented in the rest of the text. So, from this study,we propose to inquire about that sarmientino plan based on the nationalization of the port of Buenos Aires and the free navigation on the rivers. Moreover, we problematize the topic, highlighting that in the editions the port topic was not always present. On the contrary, in the 1851 and 1868 editions the author would choose to quit the chapters mentionedand he would add new “caudillos” biographies, appending semblances of Felix Aldao and el “Chacho” Peñaloza. Observing these variables, we try to rethink the importance of the port to Sarmiento, as we will try to make evident, the changings mentioned tended to center the importance of Facundo in the “caudillos”.
Keywords: Sarmiento; Facundo; Port; Caudillos